The effect of a localized fault in the planet bearing on vibrations of a planetary gear set. (July 2018) - Liu, Jing; Xu, Yajun; Shao, Yimin; Xiao, Huifang; Li, Hongwu
Dynamic characteristics of a planetary gear set can be greatly affected by a localized fault in the planet bearing. To understand the relationship between the dynamic characteristic of the planetary gear set and the localized fault sizes, a dynamic finite element model for a planetary gear set is developed. A localized fault is assumed to be located in the outer race of the planet bearing. The fault profile is defined as a rectangular one. To formulate the elastic deformations of the components and elastic contact deformations between the mating components, all components of the planetary gear set are considered as elastic bodies in the finite element model. A standard gravity is also considered in the finite element model. A Coulomb frictional model is used to formulate the frictional forces in the planetary gear set. Influences of the rotational velocity, moment, and fault width on the dynamic characteristics of the planetary gear set are discussed. The simulation results are compared with those from the previous method to validate the finite element model. It seems that the presented finite element model can be applied to simulate the dynamic characteristics of a planetary gear set caused by a localized fault in the outer race of the planet bearing.